STORM "GREEDY WATER" PALM OIL BASED ON ACADEMIC PERSPECTIVE - Gusti Rusmayadi (EnviroScienteae, 2018)
The tendentious issue of deforestation, biodiversity, "water greedy" attack ganoderma and carbon emissions continue to heat up in this decade has cornered palm plantations in Indonesia for allegedly either from outside or from inside the country becomes the base of why. To clarify these issues then this article aims to analyze the impact of oil palm plantations in terms of the water balance of plant oil palm. Water use in the oil palm plantations on average 92.05 mm/month or equivalent to 1104.5 mm/year over lamtoro stands is 3,000 mm/year, acacia 2,400 mm/year, sengon of 2,300 mm/year, amounting tea 900 mm/year, rubber amounted to 1,300 mm/year, bamboo amounted to 3,000 mm/year and teak amounted to 1,300 mm/year. The coefficient of oil palm crop of 0.93. The percentage amount of rainfall used palm oil amounted to only 39.60% of the annual rainfall. Percentage of evapotranspiration value is smaller than the value of evapotranspiration pine percentage of 64.5%, A. mangium 68.8%, amounting to 55.1% of ferns and eucalyptus (E.alba) amounted to 52.4%. Meanwhile, rubber plant has a value of 1 kc, other crops such as rice, during the period of growth has kc values between 1.05 to 1.2. Soil water content (KAT) which indicates the storage capacity of the root zone of oil lower than the root zone rubber (Rusmayadi, 2011). This is due to the oil more roots growing in the topsoil to a depth of ± 1 meter and as you go down the less. Rooting most densely contained at a depth of 25 cm. Therefore the ability of smaller savings in oil palm plantations compared to rubber, then the excess water will be removed or overflowed (Ro) is not taken ("greedy water") by palm trees. Palm oil as a commodity to be seen objectively with regard to the nature of biological (plant roots), physiological (crop coefficient), and environmental (water storage capacity). This is to straighten out the problems that it is not water but greedy oil plantation management who do not pay attention to aspects of water conservation.